Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Kue Lapis Legit Di Le Gita Cakes Pontianak - Hendi Efendi (Universitas Muhammadiyah Pontianak, 2015)
The research objective was to determine the effect of the marketing mix to purchasing decision Lapis Legit cake at Le Gita Cakes Pontianak. This type of research used in this study is a survey research. Data collection using questionnaires, observation, and secondary data. A sample of 100 respondents selected from the population coming from all consumers who buy legit layer cake at Le Gita Cakes. The sampling technique uses accidental sampling. Analysis of data using simple regression with the variables of the marketing mix (X) and the purchase decision (Y). The results showed that the regression equation is Y = 0.825 + 0.759 X. The coefficient of determination (R2) was 0.543 and the correlation coefficient (R) is equal to 0.737 or very strong, and F count larger than F table (116.216> 2.473) so it can be concluded that the regression model can be used to predict the marketing mix.